2019
DOI: 10.1111/1750-3841.14468
|View full text |Cite
|
Sign up to set email alerts
|

Bourbon and Rye Whiskeys Are Legally Distinct but Are Not Discriminated by Sensory Descriptive Analysis

Abstract: We present a Descriptive Analysis (DA) of a large representative sample (24 whiskeys) of two legally distinct types of American whiskeys: bourbon and rye whiskey (respectively distilled from a fermented “mashbill” of at least 51% corn or rye). We wanted to determine whether a trained panel could find sensory differences between these two products. We used standard DA: 11 judges were trained for 10 hours to develop a lexicon of 24 flavor, taste, and mouthfeel descriptors for the 24 whiskey samples (15 bourbons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…These results indicate that mashbill does have an influence in sensory profiles, but also that the distinction may not be so apparent when ratios of grains in mashbill recipes are closer to parity, as is likely in many commercial bourbon and rye whiskeys . This may help explain the failure to find mashbill driven differences in American whiskeys up to this point . Therefore, while the results of this research support sensory attributes stemming from the mashbill, a question remains: at what ratio do these sensory differences emerge?…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…These results indicate that mashbill does have an influence in sensory profiles, but also that the distinction may not be so apparent when ratios of grains in mashbill recipes are closer to parity, as is likely in many commercial bourbon and rye whiskeys . This may help explain the failure to find mashbill driven differences in American whiskeys up to this point . Therefore, while the results of this research support sensory attributes stemming from the mashbill, a question remains: at what ratio do these sensory differences emerge?…”
Section: Discussionmentioning
confidence: 94%
“…However, given the short range of aging times of the whiskeys in this study, it is impossible to rule out interactions emerging with longer aging. Certainly, in previous studies with whiskeys of greater age, researchers found that differences from mashbill were less apparent , which may point towards a convergence of whiskey flavours with aging. Thus, it is plausible that with longer aging time and blending practices, panellists would not be able to discriminate between the bourbon and rye whiskeys in this study.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations